Design and performance of a 3D-Printed magnetorheological fluid-based adaptive vibration isolator - Choi, Young T.; Yoo, Byungseok; Park, Jungjin; Pines, Darryll J.; Wereley, Norman M. (Frontiers in Materials, 2023)
Emerging additive manufacturing (or 3D printing) can be advantageous for developing magnetorheological fluid (MRF)-based vibration isolators (MRVIs) because their designs can be easily and efficiently customized and also in-situ fabrication and repairing can be possible. In this study, a simple and compact adaptive MRVI was fabricated by using a 3D printing method. A masked stereolithography (MSLA) 3D printer was used for the fabrication of the rubber bellow and plastic lid parts of the MRVI. The electromagnet was mounted onto the lid, the reservoir was filled with an MRF, and the lid was simply assembled with the reservoir using a 3D-printed large thread without traditionally machined components. Using a material testing machine, the damper forces of the 3D-printed MRVI were measured under a constant velocity loading condition for different magnetic fields. From these tests, the magnetic field-controllable performances of the MRVI such as the MR yield force, the dynamic force range, the dissipated energy, and the secant stiffness were obtained. For the evaluation of the long-term performance reliability of the MRVI due to the MRF sedimentation, its magnetic field-controllable performances were tracked for 156 days with the variable testing intervals. Finally, the feasibility of the 3D-printed MRVI was experimentally confirmed.